2007
DOI: 10.1021/es0703022
|View full text |Cite
|
Sign up to set email alerts
|

Steady-State and Dynamic Desorption of Organic Vapor from Activated Carbon with Electrothermal Swing Adsorption

Abstract: A new method to achieve steady-state and dynamictracking desorption of organic compounds from activated carbon was developed and tested with a bench-scale system. Activated carbon fiber cloth (ACFC) was used to adsorb methyl ethyl ketone (MEK) from air streams. Direct electrothermal heating was then used to desorb the vapor to generate select vapor concentrations at 500 ppmv and 5000 ppmv in air. Dynamic-tracking desorption was also achieved with carefully controlled yet variable vapor concentrations between 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 11 publications
(19 reference statements)
0
18
0
Order By: Relevance
“…The MSA system was found to successfully adsorb organic vapors from the airstreams, allowing for rapid regeneration of the ACC cartridge, and for the recovery of water and organic vapors as liquids. Emamipour et al [190] developed and tested a method to achieve steady-state and dynamic-tracking desorption of organic compounds from activated carbon in a bench-scale system, also exploring use of microwaves for regeneration. Activated carbon fiber cloth was used to adsorb methyl ethyl ketone (MEK) from air streams.…”
Section: Organic Gaseous Pollutants and Regeneration Of Activated Carmentioning
confidence: 99%
“…The MSA system was found to successfully adsorb organic vapors from the airstreams, allowing for rapid regeneration of the ACC cartridge, and for the recovery of water and organic vapors as liquids. Emamipour et al [190] developed and tested a method to achieve steady-state and dynamic-tracking desorption of organic compounds from activated carbon in a bench-scale system, also exploring use of microwaves for regeneration. Activated carbon fiber cloth was used to adsorb methyl ethyl ketone (MEK) from air streams.…”
Section: Organic Gaseous Pollutants and Regeneration Of Activated Carmentioning
confidence: 99%
“…It is reported that the long-term exposure to volatile organic compounds (VOCs) causes health defects such as eye and throat irritation, allergies, damage on the liver and central nervous system, etc. [Ruddy et al, 1993;Emamipour et al, 2007;Mallouk et al, 2010;Johnsen et al, 2011;Das et al, 2004]. Due to these health effects of VOCs, it is important to remove them from indoor and outdoor air.…”
Section: Introductionmentioning
confidence: 99%
“…Due to these health effects of VOCs, it is important to remove them from indoor and outdoor air. There are various methods to remove VOCs such as condensation, adsorption, catalytic oxidation and thermal oxidation [Ruddy et al, 1993;Emamipour et al, 2007;Mallouk et al, 2010;Johnsen et al, 2011;Das et al, 2004;Rafson, 1998]. Ruddy and Carrol (1) have summarized the comparative performances of these techniques regarding their advantages, limitations and operating costs.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, ACFC can be used upstream of a secondary air pollution control device such as a biofilter or a thermal oxidizer to control the concentration of the gas fed to the secondary device. The ACFC system can be operated based on user-defined constant or dynamic set-points to enhance the overall control efficiency (Emamipour et al 2007;Hashisho et al 2008).…”
Section: Introductionmentioning
confidence: 99%